2019
DOI: 10.1101/804799
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ADHD symptoms and their neurodevelopmental correlates in children born very preterm

Abstract: 23 This study investigated the association between attention-deficit/hyperactivity disorder (ADHD) 24 symptomatology in preschool-aged children who were born very preterm (<32 weeks) and cognitive 25 outcomes, clinical risk and socio-demographic characteristics. 119 very preterm children who participated 26 in the Evaluation of Preterm Imaging Study at term-equivalent age were assessed at a mean age of 4.5 27 years. Parents completed the ADHD Rating Scale IV, a norm-referenced checklist that evaluates ADHD … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
0
11
0
1
Order By: Relevance
“…Because this was a retrospective study, we did not have access to the children's ADHD phenotype. However, other studies have reported that EPT born children with ADHD are most likely to be affected by the inattentive subtype and associated intellectual disabilities 5,6,37 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Because this was a retrospective study, we did not have access to the children's ADHD phenotype. However, other studies have reported that EPT born children with ADHD are most likely to be affected by the inattentive subtype and associated intellectual disabilities 5,6,37 …”
Section: Discussionmentioning
confidence: 97%
“…These disorders have included intellectual disabilities, cerebral palsy and visual and hearing impairment 2 . In addition, speech disorders, 3 attention deficit hyperactivity disorders (ADHD), 4–6 autism spectrum disorders (ASD), 7,8 psychological problems, 9 epilepsy 10 and sleep disturbances 11 have been reported after preterm birth but have not been included in the large cohort studies on neurodevelopmental outcome after EPT birth. The long‐term sequelae of EPT birth also include dysfunction of other organ systems that manifest as respiratory dysfunction, 12 poor growth 13 and kidney dysfunction 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Other socio-economic factors selected as covariates were child’s sex, preterm delivery, ethnicity (white vs non-white), maternal age when baby was born, and maternal socioeconomic status, which was measured using the Cambridge Social Interaction and Stratification Scale, which provides a total score (33). All these variables were selected as relevant confounders as there is a higher prevalence of ADHD in males (34), preterm children (35), white children (36), children with young mothers (37), and low socio-economic status (38).…”
Section: Methodsmentioning
confidence: 99%
“…Attention deficit hyperactivity disorder (ADHD) is one of the most common mental and behavioral disorders in childhood, characterized by inattention and hyperactivity. It is easy to be complicated with various behavioral problems such as learning difficulties, emotional disorders, and tic disorders, which seriously affect the academic and emotional development of children and adolescents, and have a great impact on family relations, partnership, and social function establishment (Aricò, Arigliani, Giannotti, & Romani, 2020; Becker, 2020; Craig, Bondi, O'Donnell, Pepler, & Weiss, 2020; Drechsler et al, 2020); Hoogman, Stolte, Baas, & Kroesbergen, 2020; Montagna et al, 2020; Slobodin & Masalha, 2020; Turan, Tunctürk, Çıray, Halaç, & Ermiş, 2021. ADHD is a multifactorial disease, which is related to nerve development, accumulation or lack of trace elements, and some factors have not been identified.…”
Section: Introductionmentioning
confidence: 99%